Preparation of full-hydrophilic one-way moisture-conducting functional composite material with aperture gradient

By preparing a fully hydrophilic single-width wet-guided functional composite material with a pore diameter gradient, the problem that the single-width wet-guided functional material in the prior art is difficult to achieve continuous water transportation, and the excellent single-width wet-guided characteristics and efficient moisture transfer effect of the material are achieved.

CN119824610APending Publication Date: 2025-04-15TIANJIN POLYTECHNIC UNIV +2
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510038707.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the prior art, it is difficult to achieve continuous water transport for a single-way wet material, and the traditional double-layer assembly strategy has the problem of hydrophobic partially blocking moisture transport.

Method used

By preparing a fully hydrophilic one-way wet-guided functional composite with a pore size gradient, a combination of a hemp/viscosine hydrotubing nonwoven layer and a polylactic acid/chitosan nanofiber membrane was used to construct a fully hydrophilic composite with different fiber diameter differences and pore size differences, and the spontaneous diffusion of moisture and one-way wet-guided characteristics were achieved using Gibbs pinning theory.

Benefits of technology

The excellent single-width wet-guided properties of the material are realized, and it can efficiently transport moisture in a continuous hydrophilic system, avoiding the problem of blocking moisture transmission by hydrophobic parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BSA0000299939380000021
    Figure BSA0000299939380000021
  • Figure BSA0000299939380000022
    Figure BSA0000299939380000022
  • Figure HSA0000299939390000011
    Figure HSA0000299939390000011
Patent Text Reader

Abstract

The invention provides a preparation method of a full-hydrophilic composite material with a pore diameter gradient and a one-way moisture conduction function. A double-layer hydrophilic composite layer with a pore difference structure is prepared by adopting a means of combining an electrostatic spinning process and a spunlace non-woven process, so that the one-way moisture conduction function is realized. The preparation method comprises the following steps: firstly preparing a hemp / viscose spunlace non-woven layer, then preparing a polylactic acid / chitosan nanofiber membrane through an electrostatic spinning process, and finally compounding the hemp / viscose spunlace non-woven layer and the polylactic acid / chitosan nanofiber membrane to prepare the composite material with the one-way moisture conduction function. The two hydrophilic layers with fiber diameter difference and pore size difference are compounded through a double-layer assembly strategy, the composite material with a brand-new structure and a one-way moisture guiding function is constructed, the composite material has a good one-way liquid conveying function, the continuous one-way moisture guiding function is achieved, and the composite material is suitable for large-scale popularization and application. Wide application prospects are realized in the fields of textile clothing, medical and health materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation of a fully hydrophilic one-way moisture-conducting functional composite material with a pore size gradient, and belongs to the field of electrostatic spinning functional materials and the field of non-woven process technology. Background Art

[0002] With the increasing demand for clothing comfort, unidirectional moisture-conducting functional materials have attracted extensive attention. The realization mechanism of unidirectional moisture-conducting function includes wetting gradient effect and differential capillary effect. The raw materials of unidirectional moisture-conducting functional materials are usually natural cotton fibers or chemical fibers with different cross-sections. The currently widely used natural cotton fibers have the characteristics of hygroscopic expansion, which affects the subsequent diffusion and evaporation of water. Chemical fiber filaments with special cross-sections are usually non-degradable and will inevitably pollute the environment. In terms of wettability construction, patent CN117535880A discloses a method of preparing hexadecyl dimethyl glycidyl ammonium chloride by reacting hexadecyl dimethyl tertiary amine and epichlorohydrin, and then constructing a wetting gradient effect with nano-silica to achieve the unidirectional moisture-conducting function of the material, which is hydrophobic on one side and hydrophilic on the other side. However, the large-scale use of finishing agents will cause environmental pollution. On the other hand, patent CN116421767A prepares PAN@PDA nanofiber membrane through electrospinning process, and then prepares unidirectional moisture-conducting PAN@PDA / PCL@CUR / SF double-layer nanofiber membrane, constructing a wettability design with one side hydrophobic and the other side hydrophilic. However, there are still some problems, such as: when the material is in a continuous hydrophilic system, the transmission of water will be blocked by the hydrophobic part, that is, the fluid cannot be transmitted in the continuous hydrophilic-hydrophobic material. Therefore, based on the double-layer assembly strategy, two layers of hydrophilic materials with different fiber diameters and pore sizes are compounded to develop a fully hydrophilic unidirectional moisture-conducting functional composite material with a pore size gradient, which will help to further expand its application scenarios. Summary of the invention

[0003] The purpose of the present invention is to provide a preparation of a fully hydrophilic unidirectional moisture-conducting composite material with a pore size gradient. This is to solve the technical problem that in the prior art, a hydrophilic layer nanofiber membrane and a hydrophobic layer nanofiber membrane are often required to be combined to construct a unidirectional moisture-conducting composite material, so it is not easy to achieve continuous water transport. The differential capillary effect shows that when the difference in the size of the capillary pores inside and outside the porous material is large, the difference in additional pressure is also large, which is conducive to achieving unidirectional moisture-conducting. The pore size of the spunlace layer is larger than that of the fiber membrane layer. According to the Gibbs pinning theory, the channel from the spunlace layer to the fiber membrane layer shrinks sharply, and the shrinkage angle ɑ approaches -90 degrees. At the same time, the contact angle θ is less than 90 degrees, and moisture tends to diffuse spontaneously from the spunlace layer to the fiber membrane layer. On the contrary, the channel from the fiber membrane layer to the spunlace layer will experience a sudden expansion, causing α to approach 90 degrees, so that the material exhibits excellent unidirectional moisture-conducting properties.

[0004] The present invention provides a method for preparing a fully hydrophilic unidirectional moisture-conducting composite material with a pore size gradient, comprising the following steps:

[0005] Step 1: Preparation of hemp / viscose spunlace nonwoven layer A:

[0006] Hemp fiber and viscose fiber are opened and combed to obtain hemp fiber web and viscose fiber web respectively, and then the homogeneous fiber web is transported to a spunlace machine to prepare hemp / viscose spunlace nonwoven material A through a spunlace process;

[0007] Step 2: Preparation of polylactic acid / chitosan nanofiber membrane B:

[0008] Polylactic acid (PLA) and chitosan (CS) are dissolved in solvents to obtain PLA and CS solutions respectively, and a homogeneous PLA / CS solution is prepared by mixing the PLA solution and the CS solution. The homogeneous PLA / CS solution is then used as a spinning solution to prepare a PLA / CS hydrophilic layer nanofiber membrane B by electrospinning; Step three, preparing a unidirectional moisture-conducting fully hydrophilic pore gradient composite material C: PLA / CS nanofiber membranes of different thicknesses are deposited on one side of the hemp / viscose spunlace nonwoven material to construct a fully hydrophilic composite material C with a micro-nano layer relative thickness having different fiber diameters and pore sizes. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] 1) Figure 1 This is a plane electron microscope image of the hemp / viscose spunlace nonwoven layer A obtained in Example 1 of the present invention;

[0010] 2) Figure 2 This is a plane electron microscope image of the PLA / CS nanofiber membrane layer B obtained in Example 2 of the present invention;

[0011] 3) Figure 3 This is an electron microscopic image of the C section of the unidirectional moisture conducting functional composite material obtained in Example 3 of the present invention; DETAILED DESCRIPTION

[0012] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0013] In the following embodiments of the present invention, the analytical test methods used are described as follows:

[0014] Test 1: Water vapor permeability test

[0015] According to GB / T 12704.2-2009 standard, circular specimens with a diameter of 75 mm were prepared. Three pieces were cut from each group of specimens. The test assembly was placed in a test chamber with a moisture permeability cup filled with 34 ml of distilled water and balanced for 1 hour. The specimens were weighed every hour with an accuracy of 0.01 g. The moisture permeability of the specimens was calculated according to formula (1-1):

[0016]

[0017] Where WVT is the water vapor permeability value, m1 is the mass of the sample at the end of the test, m0 is the initial mass of the sample, A is the effective test area, and t is the test time.

[0018] Test 2: Air permeability test

[0019] The material is tested for air permeability according to GB / T 5453-1997. The test area is 20cm 2 The test pressure difference is 200Pa. The YG461H fully automatic air permeability meter is used to randomly select 10 positions for each sample for testing, and the average value of the test results is calculated as an indicator to measure the air permeability performance of the sample.

[0020] Test 3: Contact angle test

[0021] According to GB / T 30693-2014 standard, the contact angle of the material to water was measured using a contact angle meter, and the volume of distilled water was set to 2 μL.

[0022] Test 4: One-way transmission test

[0023] According to GB / T 21655.2-2019 standard, the dynamic transfer performance of liquid water in pore gradient composite materials was determined using a liquid moisture management tester. A 0.9wt% sodium chloride solution was prepared as the test liquid. The sample size was cut to 90mm long and 90mm wide. 0.22g of test liquid was dripped onto the inner surface of the material within 20s. The test time was set to 120s. The changes in the amount of water on the inner and outer surfaces during the test with the immersion time were recorded, and the size of the one-way transfer index was obtained according to formula (1-2).

[0024]

[0025] Where 0 is the one-way transfer index, ∫U B is the water absorption of the outer surface, ∫U T is the water absorption of the inner surface, and t is the test time.

[0026] Embodiment 1

[0027] A method for preparing a fully hydrophilic pore gradient composite material with a unidirectional moisture conduction function comprises the following steps:

[0028] a) Weigh a certain mass of hemp fiber and viscose fiber, loosen and comb them respectively, so that the hemp fiber web is overlapped with the viscose fiber web with a mass ratio of 40%; convey the hemp fiber web to the spunlace machine in a superimposed manner with the viscose fiber web on the upper layer and the viscose fiber web on the lower layer for spunlace process, the spunlace pressure is 1.0 MPa, and the surface density is 100 g / m 2 A layer of hydrophilic hemp / viscose spunlace nonwoven material.

[0029] b) If Figure 1 Shown is a plane electron microscope image of the hemp / viscose spunlace nonwoven layer A obtained in Example 1.

[0030] c) According to the national standard GB / T 12704.2-2009, the moisture permeability of the hemp / viscose spunlace nonwoven layer is 4800g / (m 2 ·24h).

[0031] d) According to the national standard GB / T 5453-1997, the air permeability of the hemp / viscose spunlace nonwoven layer is 620 mm / s.

[0032] e) According to the national standard GB / T 30693-2014, the water contact angle of the hemp / viscose spunlace nonwoven layer is tested and the wetting and spreading time (0°) is 1 s.

[0033] Embodiment 2

[0034] A method for preparing a fully hydrophilic pore gradient composite material with a unidirectional moisture conduction function comprises the following steps:

[0035] a) First, PLA was dissolved in trifluoroacetic acid solvent, heated and stirred at 60°C for 2 hours to obtain a PLA solution with a mass fraction of 13%; CS was dissolved in trifluoroacetic acid solvent, heated and stirred at 40°C for 4 hours to obtain a CS solution with a mass fraction of 3%; PLA solution and CS solution with a mass fraction of 30% were uniformly mixed, heated and stirred at 30°C for 10 hours, and a hydrophilic nanofiber membrane layer B was received on an aluminum foil by an electrospinning method, the spinning voltage was 18 kV, the receiving distance was 13 cm, and the flow rate of the spinning solution was 1.0 mL / h.

[0036] b) The molecular weight of PLA used in a) is 160,000; the viscosity of CS used in a) is 400 mPa.s.

[0037] c) If Figure 2 Shown is a plane electron microscope image of the PLA / CS nanofiber membrane layer B prepared in Example 2.

[0038] d) The average fiber diameter of the obtained PLA / CS fiber membrane layer is 500 nm.

[0039] e) The contact angle of the PLA / CS fiber membrane layer obtained by testing according to the national standard GB / T 30693-2014 is 68°.

[0040] Embodiment 3

[0041] A method for preparing a fully hydrophilic one-way moisture-conducting functional composite material with a pore size gradient comprises the following steps:

[0042] a) First, prepare a surface density of 130g / m 2 The hemp / viscose spunlace nonwoven layer A has a mass ratio of hemp fiber web to viscose fiber web of 50%, and is prepared by laminating the hemp fiber web on top and the viscose fiber web on the bottom under a spunlace pressure of 1.5 MPa.

[0043] b) PLA and CS were dissolved in trifluoroacetic acid solvent respectively, and the mixture was stirred at 40°C for 2 hours to obtain a 14% PLA solution and a 5% CS solution; PLA solution and CS solution with a mass fraction of 50% were uniformly mixed, and the mixture was stirred at 30°C for 8 hours to obtain a homogeneous PLA / CS spinning solution.

[0044] c) The PLA / CS spinning solution of b) is deposited on the hemp / viscose spunlace layer A of a) by an electrospinning process at a spinning voltage of 16 kV, a receiving distance of 10 cm, and a flow rate of the spinning solution of 1.5 mL / h to obtain a fully water-based pore gradient composite material C.

[0045] d) If Figure 3 The figure shows an electron microscope image of the cross section C of the unidirectional moisture-conducting functional composite material obtained in Example 3.

[0046] e) The average fiber diameter of the a) spunlace nonwoven layer A is 15 μm, the average pore size is 25 μm, and the droplet wetting and spreading time (contact angle 0°) is 1.9 s; the average fiber diameter of the c) nanofiber membrane layer is 578 nm, the average pore size is 1.35 μm, the contact angle is 65°, and the fiber membrane deposition thickness is 0.20 mm.

[0047] f) According to the national standard GB / T 12704.2-2009, the moisture permeability of the composite material is 5000g / (m 2 ·24h).

[0048] g) According to the national standard GB / T 5453-1997, the air permeability of the composite material is 23 mm / s.

[0049] h) According to GB / T 21655.2-2019, the one-way transmission index of the composite material is 422.

[0050] The above embodiments are used to further illustrate the present invention, but the present invention is not limited to these specific embodiments. Any modification, equivalent substitution and improvement made within the spirit and principle of the present invention should be understood to be within the protection scope of the present invention.

Claims

1. Preparation of a fully hydrophilic one-way moisture-conducting composite material with a pore size gradient, characterized in that: The following steps are involved: Step 1: Preparation of hemp / viscose spunlace nonwoven layer A: Hemp fiber and viscose fiber are opened and combed to obtain hemp fiber web and viscose fiber web respectively, and then the homogeneous fiber web is transported to a spunlace machine to prepare hemp / viscose spunlace nonwoven material A through a spunlace process; Step 2: Preparation of polylactic acid / chitosan nanofiber membrane B: Polylactic acid (PLA) and chitosan (CS) are dissolved in solvents to obtain solutions, and a homogeneous PLA / CS solution is prepared by mixing the PLA solution and the CS solution. The PLA / CS hydrophilic layer nanofiber membrane B is prepared by electrospinning using the homogeneous PLA / CS solution as a spinning solution. Step 3: Preparation of a unidirectional moisture-conducting fully water-type pore gradient composite material C: PLA / CS nanofiber membranes of different thicknesses were deposited on one side of the hemp / viscose spunlace nonwoven material to construct a fully hydrophilic composite material C with different fiber diameter differences and pore size differences and a micro-nano layer relative thickness.

2. The method for preparing a fully hydrophilic one-way moisture-conducting functional composite material with a pore size gradient according to claim 1, characterized in that: The mass ratio of the hemp fiber web and the viscose fiber web in step one is 30-70% respectively; the homogenized hemp fiber web and the viscose fiber web in step one are: the hemp fiber web is in the upper (lower) layer and the viscose fiber web is in the lower (upper) layer, and are transported to the spunlace machine for the spunlace process in a superimposed manner, and the spunlace pressure is 1-5MPa.

3. The method for preparing a fully hydrophilic one-way moisture-conducting composite material with a pore size gradient according to claim 1, characterized in that: The solvent for preparing the PLA / CS nanofiber membrane B in step 2 is any one or both of trifluoroacetic acid and acetic acid; the molecular weight of PLA in step 2 is 100,000-200,000, the mass fraction of the solution is 10-30%, the temperature of hot stirring dissolution is 20-60°C, and the time is 1-8h.

4. The method for preparing a fully hydrophilic one-way moisture-conducting functional composite material with a pore size gradient according to claim 1, characterized in that: In the step 2, the CS solvent is prepared as any one or both of trifluoroacetic acid and acetic acid, the CS viscosity is greater than 400 mPa·s, the mass fraction of the solution is 3-10%, the temperature of hot stirring dissolution is 20-40° C., and the time is 1-8 hours.

5. The method for preparing a fully hydrophilic one-way moisture-conducting functional composite material with a pore size gradient according to claim 1, characterized in that: The solvent of PLA / CS nanofiber membrane B is any one of trifluoroacetic acid and acetic acid or both, and the PLA / CS spinning solution is mixed according to the mass proportion of PLA solution of 10-80%; the temperature of hot stirring dissolution is 20-60°C, the time is 1-24h, and the defoaming is allowed to stand for 2-5h.

6. The method for preparing a fully hydrophilic one-way moisture-conducting functional composite material with a pore size gradient according to claim 1, characterized in that: The electrospinning process parameters of step 2 are: voltage 16-20 kV, receiving distance 10-15 cm, and flow rate of spinning solution 1-2 ml / h.

7. The method for preparing a fully hydrophilic one-way moisture-conducting functional composite material with a pore size gradient according to claim 1, characterized in that: The surface density of the hemp / viscose spunlace nonwoven material A in step 3 is 100-130 g / m 2 The stacking method is that the hemp fiber mesh is on the upper layer and the viscose fiber mesh is on the lower layer. The wetting time from the water droplet contacting the material to the spread of 0° (contact angle) is less than 2s, the fiber diameter is 10-20μm, and the average pore size is greater than 25μm.

8. The method for preparing a fully hydrophilic one-way moisture-conducting functional composite material with a pore size gradient according to claim 1, characterized in that: The thickness of the PLA / CS nanofiber membrane deposited in step three is 0.1-0.3 mm, the fiber diameter is 400-600 nm, the average pore size is less than 2 μm, and the water contact angle is 60°-80°.

9. The method for preparing a fully hydrophilic one-way moisture-conducting functional composite material with a pore size gradient according to claim 1, characterized in that: The one-way moisture-conducting fully hydrophilic pore gradient composite material is composed of a double-layer hydrophilic spunlace nonwoven layer and a nanofiber membrane layer with fiber diameter scale differences and pore size differences.

10. The method for preparing a fully hydrophilic one-way moisture-conducting composite material with a pore size gradient according to claim 1, characterized in that: The moisture permeability of the one-way moisture-conducting fully hydrophilic pore gradient composite material is ≥4500g / (m 2 ·24h), air permeability ≥18mm / s, one-way transmission index ≥150.

Citation Information

Cited By

  • Triple gradient structure one-way moisture conduction non-woven composite fabric and preparation method thereof

    CN119749022A

  • Biomass solid waste-based saline-alkali soil surface desalting structure based on gradient pore regulation and control and preparation and use methods of biomass solid waste-based saline-alkali soil surface desalting structure

    CN120917941A